Metabolism of the Antituberculosis Drug Ethionamide - Nuno Vale (2013)
Ethionamide (ETH) is an important second-line antituberculosis drug used for the treatment of patients infected with multidrug-resistant Mycobacterium. Although ETH is a structural analogue of isoniazid (INH), both are pro-drugs that need to be activated by mycobacterial enzymes to exert their antimicrobial activity. ETH mechanism of action is thought to be identical to INH although the pathway of activation is distinct from that of INH. ETH is activated by an EthA enzyme, leading to the formation of an S-oxide metabolite that has considerably better activity than the parent drug. This review comprehensively examines the aspects related with the metabolism of ETH since its discovery up to today.